1989
DOI: 10.1161/01.res.64.5.890
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying atriopeptin-induced increases in hematocrit and vascular permeation in rats.

Abstract: Infusion of atriopeptin into humans and animals induces diuresis, natriuresis, hemodynamic changes, and an increase in arterial hematocrit. The objective of the present study was to elucidate the mechanism(s) responsible for the increase in hematocrit in rats given atriopeptin-24 (AP-24). Infusion of AP-24 for 30 minutes increased large vessel and total vascular hematocrits by 10-15% while decreasing microvascular hematocrits by 9-26% in numerous tissues. Regional vascular permeation by [131I] bovine serum alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
4
13
1
Order By: Relevance
“…Previous studies from our laboratory have demonstrated that exogenously administered ANP causes a significant reduction of blood volume and produces transudation of radiolabeled albumin, particularly in fetal skin, but also in muscle , adrenal, bone, kidney, and gut (7). ANPinduced increases in vascular permeation independent of renal effects have been identified in adult animal models as well (21)(22)(23). The correlation between increased ANP concentrations and significantl y expanded extracellular fluid volume in the anemic fetuses is consistent with the hypothesis that ANP may directly or indirectly increase capillary filtration of fluid.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies from our laboratory have demonstrated that exogenously administered ANP causes a significant reduction of blood volume and produces transudation of radiolabeled albumin, particularly in fetal skin, but also in muscle , adrenal, bone, kidney, and gut (7). ANPinduced increases in vascular permeation independent of renal effects have been identified in adult animal models as well (21)(22)(23). The correlation between increased ANP concentrations and significantl y expanded extracellular fluid volume in the anemic fetuses is consistent with the hypothesis that ANP may directly or indirectly increase capillary filtration of fluid.…”
Section: Discussionsupporting
confidence: 64%
“…ANP causes significant increases in albumin permeation in adult models (2,12). However, the absolute values of fetal albumin clearance we observed in the control state were 5-to 20-fold higher than those that Williamson cJt 01.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the absolute values of fetal albumin clearance we observed in the control state were 5-to 20-fold higher than those that Williamson cJt 01. (2) described in the adult rat. This finding is consistent with the observation that the capillary filtration coefficient in the fetal sheep is 5-10 times greater than in the adult (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right iliac artery cannula was connected to a Statham P50 pressure transducer for monitoring blood pressure as well as for arterial blood sampling, and the left iliac artery cannula was connected to a withdrawal pump for assessment of regional blood flow. The trachea also was Blood flow (expressed as milliliters blood -gram wet weight-' i min-') was measured by injecting 15 Mzm 85Sr-microspheres (NEN Research Products) as described in previous publications (20,21).…”
Section: Skin Chamber Insertionmentioning
confidence: 99%